2015
DOI: 10.1016/j.bpj.2015.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Surfactant Proteins Strongly Induce Negative Curvature

Abstract: The hydrophobic surfactant proteins SP-B and SP-C greatly accelerate the adsorption of vesicles containing the surfactant lipids to form a film that lowers the surface tension of the air/water interface in the lungs. Pulmonary surfactant enters the interface by a process analogous to the fusion of two vesicles. As with fusion, several factors affect adsorption according to how they alter the curvature of lipid leaflets, suggesting that adsorption proceeds via a rate-limiting structure with negative curvature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…For mixtures of N&PL and CLSE, the L γ phase begins to disappear at X CLSE = 0.7, when the net molecular charge has fallen only by 5% to −0.095 (Table S1.B). In addition to their electrostatic effect, the proteins induce large changes in the spontaneous curvature of the lipids; 40 they may also alter flexibility of the leaflets. These effects seem more likely to explain the inhibition of the L γ phase than a reduction in net charge.…”
Section: Discussionmentioning
confidence: 99%
“…For mixtures of N&PL and CLSE, the L γ phase begins to disappear at X CLSE = 0.7, when the net molecular charge has fallen only by 5% to −0.095 (Table S1.B). In addition to their electrostatic effect, the proteins induce large changes in the spontaneous curvature of the lipids; 40 they may also alter flexibility of the leaflets. These effects seem more likely to explain the inhibition of the L γ phase than a reduction in net charge.…”
Section: Discussionmentioning
confidence: 99%
“…7% PS+PI are reported in LBs [47]) can promote non-lamellar phases in conditions characterized by very low water content, low pH and high Ca 2+ concentrations [52]. Additionally, non-lamellar structures can be stabilized by the presence of SP-B and SP-C, as reported in a model system composed of DOPC:DOPE [53]. Indeed in vitro experiments using extract of broncho-alveolar lavages from sheep lungs reported by Teubner et al demonstrated lyotropicmesomorphism induced by the percentage of water in the system [54].…”
Section: Discussionmentioning
confidence: 99%
“…Given that DPPC can be packed more tightly than unsaturated lipids, this could be relevant for reaching low surface tensions during exhalation. The change in curvature could also explain, to some extent, SP-C-mediated lipid adsorption, which has been suggested to occur through a negatively curved stalk in cooperation with SP-B (60)(61)(62). For such a structure to occur, SP-B and SP-C would need to generate membrane curvature, a condition that although already demonstrated (9,63,64), does not provide enough mechanistic insights to determine how this process is accomplished.…”
Section: Sp-c Induces Phase Segregationmentioning
confidence: 99%